PERLINDUNGAN HUKUM KEPADA ORANG DENGAN PERMASALAHAN KESEHATAN JIWA SAAT COVID-19 - Vanessa Mathilde Harum (Fakultas Hukum Universitas Tarumanagara, 2022)
The pandemic is not over yet. Covid-19 ass a sensitive topic for Indonesian. Positive cases of Covid-19 areincreasing day by day which makes people in Indonesia more afraid. When we are exposed to the virus, we mustimmediately quarantine or go directly to the hospital if the symptoms are severe. The whole community, fromchildren to the elderly, can feel the impact of this virus, not to mention if they are exposed to Covid- 19 whichrequires us to quarantine. This quarantine activity that we do alone can cause anxiety and boredom which canaf ect our mental or mental health. There are so many cases in Indonesia who experience mental disorders dueto quarantine for too long, this is experienced from children to the elderly. Mental health that occurs is anemotional, psychological, and social condition. This condition af ects how a person feels, thinks, and how tosurvive in the midst of these conditions. Mental health also af ects the decision-making process and how aperson deals with stress. However, from the research results obtained, there is a relationship between theCovid-19 pandemic and a person's mental health. Fear, worry and stress what he experienced was a normalresponse he felt, moreover the Covid-19 virus is very dangerous for our bodies which can attack our organs andalso this virus has taken the lives of many Indonesian people. So it is certain that many people who are exposedto this virus experience mental health problems.